2019
DOI: 10.7341/20191534
|View full text |Cite
|
Sign up to set email alerts
|

An innovation policy framework for upgrading firm absorptive capacities in the context of catching-up economies

Abstract: The paper addresses the 'regional innovation paradox' referring to the lower capacity to absorb public funds earmarked for the promotion of innovation in the peripheral regions. The key aim is thus to propose and test a conceptual framework of tailored innovation policy routes that aim at stimulating absorptive capacities of firms. Literature analysis helps to distill determinants of absorptive capacity at firm and system levels. Analysis of innovation policies applied by the Central and Eastern European (CEE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Grossman & Helpman, 1980, 1991b) and empirical research (e.g. Chiappini, 2014), especially in the context of innovation and entrepreneurship (Crudu, 2019) as well as catchingup economies (Paliokaite, 2019). The results for PATENT affirm the role of technology for structural similarities.…”
Section: Figure 1 Semiparametric and Nonparametric Estimation Resultsmentioning
confidence: 68%
“…Grossman & Helpman, 1980, 1991b) and empirical research (e.g. Chiappini, 2014), especially in the context of innovation and entrepreneurship (Crudu, 2019) as well as catchingup economies (Paliokaite, 2019). The results for PATENT affirm the role of technology for structural similarities.…”
Section: Figure 1 Semiparametric and Nonparametric Estimation Resultsmentioning
confidence: 68%
“…Furthermore, this study develops a framework to explore the processes through which open innovation intermediaries fill the aforementioned roles. In the context of transition economies, but also in general, SMEs often lack the innovation capabilities necessary to access and enter a business field featuring high turbulence and risk (Paliokaite, 2019). This study strongly suggests that cluster initiatives as open innovation intermediaries can provide effective assistance to the innovation processes of SMEs.…”
Section: Implication For Research and Practicementioning
confidence: 81%
“…It shows that public entrepreneurs, acting in an enabling way, are crucial to start such triple helix collaboration initiatives with MNEs. It is intended to highlight the diversity of strategies and BA collaborations, offering potential insights for policy-makers interested to support upgrading through tailored and selective policies (rather than a one-size-fits-all approach), following Havas (2015) and Paliokaitė (2019).…”
Section: Discussionmentioning
confidence: 99%
“…Public research, on the other hand, plays a more significant role during the firms' ongoing projects (Cohen et al 2002). Furthermore, Paliokaitė (2019) and Havas (2015) observed that firms face different needs, possess distinctive capabilities and engage in different types of BA collaborations, but innovation policies (esp. in the CEE countries) tend to neglect this diversity, focusing mainly on strategic, long-term R&D (Havas 2015).…”
Section: Business-academia Collaborations and Multinational Enterprisesmentioning
confidence: 99%